LINKING SURVEY AND ADMINISTRATIVE RECORDS: MECHANISMS OF CONSENT - Sakshaug, Joseph W. (Sociol Methods Res, 2012)
Survey records are increasingly being linked to administrative databases to enhance the survey data and increase research opportunities for data users. A necessary prerequisite to linking survey and administrative records is obtaining informed consent from respondents. Obtaining consent from all respondents is a difficult challenge and one that faces significant resistance. Consequently, data linkage consent rates vary widely from study-to-study. Several studies have found significant differences between consenters and non-consenters on socio-demographic variables, but no study has investigated the underlying mechanisms of consent from a theory-driven perspective. In this study, we describe and test several hypotheses related to respondents’ willingness to consent to an earnings and benefit data linkage request based on mechanisms related to financial uncertainty, privacy concerns, resistance towards the survey interview, level of attentiveness during the interview, the respondents’ preexisting relationship with the administrative data agency, and matching respondents and interviewers on observable characteristics. The results point to several implications for survey practice and suggestions for future research.